PERANCANGAN AKSES OPERATOR BERDASARKAN PRINSIP ERGONOMI PADA UNIT MODULAR LIGHTING TOWER DI PT. XYZ - Nursim; Winarno; Muhammad Nazmi Saputra (Technologic, 2019)
The customer's voice regarding maintenance of the components inside the cabin is hampered and the control panel continues to be uncomfortable due to the lack of ergonomics in the Lighting Tower design. Access to maintenance is obstructed by the walls and cabin doors and then the control panel, which is even more than the operator control panel, needs to bend while doing the Lighting Tower. The customer's voice is processed by the method of why the analysis is to find out the root of the problem. Then improvements are made to the design of the operator's access design based on ergonomic principles on the Modular Lighting Tower unit that is related to the control panel. The results of the treatment are maintenance and ergonomic operation with maintenance not hampered by cabin walls or doors and the operator control panel door does not need to bend.